PEMBINAAN MASYARAKAT PERAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN PENDAPATAN UMKM DI KABUPATEN PRINGSEWU (Jurnal PkM Pemberdayaan Masyarakat, 2021)
The development of information technology in Indonesia grows following the literacy level of society, from urban areas to villages or small areas. Information technology in the business sector itself has received quite a good response among business actors. Utilization of Information Technology in MSMEs as an Innovation As an innovation by MSMEs, of course, information technology has a number of advantages, including providing opportunities to expand market access, as a marketing medium, and many more. From the results of the initial analysis, it was found that the level of understanding of MSMEs in the Pringsewu area was still low regarding the use of information technology. From the results of the distribution of questions conducted before the training, there were 76% of participants did not understand the use of internet technology as a medium for promoting MSME products. After providing assistance and practice at the STMIK Pringsewu Lab, there was an increased understanding of more than 90% of MSME actors being able to utilize internet technology as a marketing medium.